Interdisciplinary teamworking in rehabilitation: experiences of change initiators in a national rehabilitation hospital - Lauren Christophers; Zsofia Torok; Aine Trayer; George Chao-Chi Hong; Aine Carroll (BMC Health Services Research)
Abstract Objective This study aimed to qualitatively explore the experiences of healthcare professionals implementing changes (as change initiators) and operationalizing interdisciplinary teamwork in a rehabilitation service within the Irish healthcare system. Data sources Data for this study were collected through focus group discussions with change initiators involved in interdisciplinary team initiatives at a rehabilitation service in Ireland. Review methods A reflexive thematic analysis was employed to analyse the focus group data, which involved identifying patterns and themes within the narratives provided by participants. Results Three overarching themes emerged from the analysis: 1. "Nature of the Battle for Change", 2. "Characteristics of the 'Status Quo' and Contradictions to IDT Working," and 3. "Power and Identity: Threats to Hierarchy and Status". These themes shed light on the challenges faced in implementing interdisciplinary teamwork, particularly the perceived threats to individual power and professional identity within hierarchical healthcare structures. Conclusion Implementing healthcare changes, especially in historically hierarchical healthcare systems is complex. Interdisciplinary team rehabilitation can challenge the status quo, posing adoption barriers. A nuanced, bottom-up approach is recommended, emphasizing long-term coalition building, continuous professional development, and early discussions about hierarchy and status. These recommendations offer practical guidance for stakeholders seeking to implement interdisciplinary, person-oriented approaches in rehabilitation practices, facilitating better anticipation and resolution of challenges, and ultimately improving care delivery and patient outcomes.